An Assessment of the Construct Validity of Three Job Evaluation Methods: a Field Experiment - Collins, Judith M.; Muchinsky, Paul M. (Academy of Management Journal, 1993)
Federal statutes recommend the analysis of four job attributes as measures of job worth, and the National Academy of Sciences recommends using one job evaluation method across classifications in an organization. The results of this construct validity study showed that the correctness of evaluations based on the four factors is questionable, as is the use of a single method across classifications.